Aneurysmal Subarachnoid Hemorrhage in a 68-Year-old Hyperglycemic Female Patient: Case Report and Literature Review - Paul Marcel Morgan (University Library System, University of Pittsburgh, 2019)
Background: While hyperglycemia is intimately associated with uncontrolled diabetes mellitus (DM), recent clinical studies have demonstrated that hyperglycemia is also present in the early acute phase of stroke and is associated with poor prognosis and increased long-term mortality. About half of patients with acute hemorrhagic stroke also present with hyperglycemia upon admission. But more than 50% of patients with acute hemorrhagic stroke develop hyperglycemia even without a previous history of DM. This sheds new light on the relationship between DM, hyperglycemia, and hemorrhagic stroke, with a pathophysiology that is perhaps more profound than is conventionally understood. The Case: We report a case of a 68-year-old female, with a history of DM Type 2 and stage 3 hypertension who presents to the emergency room (ER) at the Western Regional Hospital in Belmopan City, Belize, with hemorrhagic stroke and hyperglycemia. Diffuse subarachnoid hemorrhage was found in the frontal, temporal, and parietal regions. Mild intraventricular hemorrhage was also observed in the frontal horns and basal cisterns. And small areas of intraparenchymal hemorrhage were present in the frontal lobes. The patient was stabilized and treated conservatively with calcium channel blockers, and diuretics. Conclusion: Despite a unifying consensus that is still pending, maintaining glucose levels between 110-120 mg/dl by using continuous insulin infusions after traumatic brain injury or aneurysmal subarachnoid hemorrhage may carry some clinical benefit with slightly improved outcome.